Munchausen syndrome by proxy: a case report - Şahin, Figen; Kuruoğlu, Aslı; Işık, Ali Fuat; Karacan, Elvan; Beyazova, Ufuk (The Turkish Journal of Pediatrics, 2002)
Munchausen syndrome by proxy (MSBP) is a serious form of child abuse, which is characterized by a child with symptoms and signs of an illness that have been fabricated by the mother. Here, we present a case of MSBP, who at four months of age was brought to our hospital by her mother because of rectal bleeding. The patient underwent many invasive procedures until the diagnosis of MSBP was finally considered. The mother reported no rectal bleeding for almost a year, during follow-up at the well-child outpatient department. At 19 months of age, another episode of rectal bleeding occurred, when a bloody diaper was presented to the attending physicians. The blood group and DNA analysis of the blood in the diaper confirmed the diagnosis. The case was reported to the social services and the patient was placed in the custody of her father’s sister. The mother is still undergoing treatment in our psychiatry department.